A Genetically Encoded β‐Lactamase Reporter for Ultrasensitive 129Xe NMR in Mammalian Cells. (15th June 2016) - Wang, Yanfei; Roose, Benjamin W.; Palovcak, Eugene J.; Carnevale, Vincenzo; Dmochowski, Ivan J.
Abstract: Molecular imaging holds considerable promise for elucidating biological processes in normal physiology as well as disease states, but requires noninvasive methods for identifying analytes at sub‐micromolar concentrations. Particularly useful are genetically encoded, single‐protein reporters that harness the power of molecular biology to visualize specific molecular processes, but such reporters have been conspicuously lacking for in vivo magnetic resonance imaging (MRI). Herein, we report TEM‐1 β‐lactamase (bla) as a single‐protein reporter for hyperpolarized (HP) 129 Xe NMR, with significant saturation contrast at 0.1 μm . Xenon chemical exchange saturation transfer (CEST) interactions with the primary allosteric site in bla give rise to a unique saturation peak at 255 ppm, well removed (≈60 ppm downfield) from the 129 Xe‐H2 O peak. Useful saturation contrast was also observed for bla expressed in bacterial cells and mammalian cells.